Attenuation of Brain Nitrostative and Oxidative Damage by Brain Cooling during Experimental Traumatic Brain Injury. (24th January 2011) - Kuo, Jinn-Rung; Lo, Chong-Jeh; Chang, Ching-Ping; Lin, Mao- Tsun; Chio, Chung-Ching
Abstract : The aim of the present study was to ascertain whether brain cooling causes attenuation of traumatic brain injury by reducing brain nitrostative and oxidative damage. Brain cooling was accomplished by infusion of 5 mL of 4 ° C saline over 5 minutes via the external jugular vein. Immediately after the onset of traumatic brain injury, rats were randomized into two groups and given 37 ° C or 4 ° C normal saline. Another group of rats were used as sham operated controls. Behavioral and biochemical assessments were conducted on 72 hours after brain injury or sham operation. As compared to those of the sham-operated controls, the 37 ° C saline-treated brain injured animals displayed motor deficits, higher cerebral contusion volume and incidence, higher oxidative damage (e.g., lower values of cerebral superoxide dismutase, catalase, glutathione peroxidase and glutathione reductase, but higher values of cerebral malondialdehyde), and higher nitrostative damage (e.g., higher values of neuronal nitric oxide synthase and 3-nitrotyrosine). All the motor deficits and brain nitrostative and oxidative damage were significantly reduced by retrograde perfusion of 4 ° C saline via the jugular vein. Our data suggest that brain cooling may improve the outcomes of traumatic brain injury in rats by reducing brain nitrostative and oxidative damage.